Chadors and Graffiti, EU Flags and Iconic Bodies: Four Contemporary Visual Artists - Maria Petrides (Opticon1826, 2006)
Contemporary art stretches beyond the boundaries of an individual medium and of a single national border. With this encouragement of diversity, fluidity and mobility, art becomes a form of social empowerment by the very surrender of singularity. Reviewing the work of four artists - the Turkish-Cypriot fashion designer and installation/video artist Hussein Chalayan; the British graffiti artist known as Banksy; the New York installation artist Spencer Tunick; and the New York-based multimedia artist Anna Lascari - this piece of commentary aims to show how, in the late twentieth and early twentyfirst century, certain art expresses its resistance through various media: whether it be social or political resistance, or resistance to any type of ‘conformity’ which may restrict the potential found in mobility and hybridity.